Pasantía En La Agencia De Aduanas Servicios Aduaneros Integrados S.A.S Nivel 1 - Agencia De Aduanas Servadi S.A.S Nivel 1 (2025)
Customs agencies, authorized by DIAN, play a crucial role in international trade as they guarantee compliance with laws within the import and export processes. The Customs Agency Integrated Customs Services S.A.S. Level 1 – Customs Agency Servadi S.A.S Level 1, was established in 1979, has a wide portfolio of services, has branches in Cali, Buenaventura, Bogotá and Cartagena. The company distinguishes itself by offering high quality, security and efficiency services. And, for an international trade student, completing an internship in this company is an excellent opportunity to apply the theoretical knowledge gained during their professional career.